A nationwide cross-sectional study in Saudi Arabia for the assessment of understanding and practices of clinicians towards personalized genetic testing - Mohy Uddin; Ahmad Deeb; Husam Ardah; Marwan Nashbat; Mohammad Yahya Ayoub; Majid Alfadhel (Scientific Reports)
Abstract In order to plan and facilitate the culture of personalized / precision medicine in medical practices within any healthcare institution, it is requisite for healthcare professionals like clinicians to have a clear understanding and approach towards the practices of personalized genetic testing. This nationwide cross-sectional study aimed to measure the perceptions and knowledge of clinicians towards personalized genetic testing and assess their current practices of personalized genetic testing in clinical settings through an online self-administered questionnaire in Saudi Arabia. The results of the study revealed that almost two-fifths of participants were responsible for ordering genetic tests directly (39.0%). The main concerns of the participants were the lack of clinical practice guidelines on personalized genetic tests (50.0%) and the cost of these tests (50.9%). The participants revealed that the genetic tests had influenced the patients’ treatment plans (50.0%) and helped them understand the risks of their patients’ disorders (52.3%). The study revealed a gap in understanding and implementing personalized genetic testing in Saudi Arabia, with enthusiasm tempered by challenges like insufficient knowledge, lack of guidelines, and practical applications’ barriers. Effective integration of genetic testing into clinical practice should focus on enhancing medical education, developing clinical guidelines, and improving patient awareness about genetic tests that can lead to an improved personalized healthcare approach.